Integrating Pancasila Student Profile and Islamic Education: A Character Education Model within the Independent Curriculum - Syarifah; Yoyoh Badriyyah; Muwahidah Nurhasanah; Luthfia Hanifatus Saiyidah (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2026)
The Independent Curriculum in Indonesia emphasizes character education through the Pancasila Student Profile Strengthening Project (P5). However, existing studies generally examine P5 implementation and Islamic character education within Islamic Religious Education (PAI) as separate domains, leaving a conceptual gap regarding their pedagogical integration. This study aims to analyze how P5 values are operationally integrated with Islamic educational principles in character formation within the Independent Curriculum. This research employed a qualitative descriptive case study approach. Data were collected through semi-structured interviews, non-participant observations, and document analysis involving school leaders, P5 coordinators, teachers, and parents. Data analysis followed the interactive model of Miles, Huberman, and Saldaña, encompassing data reduction, data display, and conclusion drawing, supported by methodological and source triangulation to ensure credibility. The findings indicate that P5–PAI integration is implemented through a structured instructional process across three stages: planning, implementation, and evaluation. At the planning stage, P5 dimensions are aligned with Islamic character values within curriculum documents and lesson designs. Implementation occurs across intra-curricular, co-curricular, and extracurricular activities through habituation-based religious practices and contextual learning. Evaluation emphasizes continuous character monitoring supported by teacher observation and home–school collaboration rather than solely academic assessment. This study contributes theoretically by conceptualizing an operational integration model of P5 and Islamic character education, positioning national character education policy as a pedagogical resource within Islamic education. Practically, the findings provide a contextual reference for educators and curriculum developers implementing P5 within PAI learning in alignment with the objectives of the Independent Curriculum